METHODOLOGICAL ENSURING THE FORMATION OF THE DEVELOPMENT STRATEGY OF THE EXPORT-IMPORT ACTIVITIES OF ENTERPRISES - Балюк, Юлія С. (Journal of Strategic Economic Research, 2024)
The recovery strategies for Ukraine’s economy involve developing export-import activities of enterprises. Consequently, addressing issues related to the formation of a strategy for the development of export-import activities of enterprises is relevant. The article presents a methodical approach to forming strategies for the development of export-import activities at enterprises, which consists of relevant stages and includes the content of tasks for each stage, methods of task solution, and expected results. The system of indicators of the development of export-import activities is proposed. The system of indicators must meet the relevant requirements. The subject of the study is the assessment of the development of export-import activities. The goal is to justify the application of the mixture separation task to determine changes in the processes of export-import activities development. The task is to develop methodical support for forming strategies for the development of export-import activities at enterprises. General scientific methods are employed, such as system analysis to determine the substantive essence of export-import activity development, cluster analysis to address the task of partitioning a set of indicator values into homogeneous subsets, and descriptive statistical tools to ascertain numerical characteristics of indicator value distributions. It is recommended to solve the problem of separating the mixture in order to assess the development of export-import activity, namely to determine the stage of changes in its indicators. This makes it possible to identify the development process over time, its stages. The obtained results include the methodical support for the formation of a strategy for the development of export-import activities based on the conducted generalization and systematization of recommendations from domestic scientists. Its analytical basis includes identifying changes that determine development for each characteristic of export-import activities. The conclusion is that solving the task of separating a mixture allows for identifying changes that drive development and objectively assessing the state of export-import activities to substantiate indicator values in a strategy that ensures its effectiveness.